2011
DOI: 10.1891/1559-4343.13.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Reanalyzing a Randomized Controlled Trial of Combination Antidepressant Treatment With Mirtazapine: Confidence Intervals Suggest Substantial Uncertainty

Abstract: This article subjects a randomized controlled trial (RCT) published in the American Journal of Psychiatry to a methodological and statistical critique, including a reanalysis of the effect size statistics presented. The published trial tested the use of combination antidepressants (mirtazapine coprescribed with either bupropion, venlafaxine, or fluoxetine) at treatment initiation as compared with fluoxetine monotherapy. The authors report that combination therapy was effective, with a number-needed-to-treat (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The authors concluded that combination therapy was more effective but failed to report confidence intervals for their analyses. Lacasse (2011), reanalyzed the data and calculated confidence intervals for the reported Number Needed to Treat and argues that, in fact, there is "substantial uncertainty" (p. 152), and therefore combination therapy cannot be recommended on the basis of this study. Further, problems in statistical reporting may cause substantive claims to become unfalsifiable (see generally Popper, 1959Popper, /1968), among other issues.…”
Section: Chapter 3 Methodology Purpose and Outline Of The Studymentioning
confidence: 99%
“…The authors concluded that combination therapy was more effective but failed to report confidence intervals for their analyses. Lacasse (2011), reanalyzed the data and calculated confidence intervals for the reported Number Needed to Treat and argues that, in fact, there is "substantial uncertainty" (p. 152), and therefore combination therapy cannot be recommended on the basis of this study. Further, problems in statistical reporting may cause substantive claims to become unfalsifiable (see generally Popper, 1959Popper, /1968), among other issues.…”
Section: Chapter 3 Methodology Purpose and Outline Of The Studymentioning
confidence: 99%
“…Confidence intervals have been put forth as one solution to the problems surrounding p values (e.g., Fidler et al, 2004; Gardner & Altman, 1986; Rothman, 1978). Although potentially useful in practice (e.g., Lacasse, 2011), confidence intervals have also been difficult for researchers to interpret (Greenland et al, 2016; Hoekstra et al, 2014; Poole, 1987). A confidence interval is an interval estimate, calculated from sample data, for some population parameter (Cumming & Finch, 2005).…”
Section: Schools Of Statistical Inferencementioning
confidence: 99%
“…Mercer (2015) writes that editors and reviewers of academic journals play a central role in improving the rigor of academic literature and presents recommendations for the peer review process. This is an important issue that is increasingly recognized in the broader scientific community (Smith, 2006;Lacasse, 2011), and we are pleased to publish this article.…”
mentioning
confidence: 99%